Effect of orientation and container shape on the growth and development of chile ancho pepper cultivated in greenhouse - Gómez-González, Adrián; Reyes-Contreras, José Guadalupe; García-Herrera, Eduviges Javier; Pimentel-López, José; Silos-Espino, Héctor (Revista Mexicana de Ciencias Agrícolas, 2019)
In this work the effect of solar radiation on greenhouse environmental conditions and effect on the substrate placed in containers vertically and horizontally for chile ancho pepper cultivation was analyzed. It was found that during the months of August 26 to October 17, there is a solar radiation between 246.91 (9:00 h) to 642 (12:00 h) W m-2. The above, induced inside the greenhouse a differential CO2 content at 9:00 h (853 ppm). In growth and yield of the chili plant, the plants cultivated in horizontal containers stood out the height (98.88 cm) and in dry weight (34.08 g) per plant. Horizontal containers showed a greater correlation between root and volume fresh weight variables of 99%, while the lowest was between leaf area and yield. Therefore, we conclude that in greenhouse chili cultivation it is recommended to use horizontal containers facing south to make efficient their yield by at least 25%.